A Retrospective Analysis of Selected Opioids in Hair of Workplace Drug Testing Subjects - Stowe, G Neil; Paulsen, Ryan B; Hill, Virginia A; Schaffer, Michael I (Journal of analytical toxicology, 2019)
Opioids, both naturally occurring and semisynthetic, are effective pain management medications, but also possess the potential for abuse. Analyses of over 37,000 head and body hair samples containing codeine, morphine, hydrocodone, hydromorphone, oxycodone or oxymorphone provide a view of use habits of workplace-testing subjects that cannot be obtained from fluid matrices results. Testing was performed using FDA cleared immunoassays using either 2 ng morphine or oxycodone per 10 mg hair as calibrators. Non-negative screening samples were washed with an extended aqueous wash procedure followed by LC–MS-MS confirmation at a cutoff concentration of 2 ng opioid per 10 mg hair. The LC–MS-MS method measured codeine, morphine, 6-acetylmorphine, hydrocodone, hydromorphone, oxycodone and oxymorphone with an administratively established LOQ of 0.50 ng opioid per 10 mg hair. The linear range was 0.50–100 ng morphine per 10 mg hair, and 0.50–150 ng opioid per 10 mg hair for all other measured analytes. For all analytes, within run precision was ≤5.4%, and between-run precision was ≤6.4%. Analysis of samples containing metabolites found that, among codeine positive samples, 97% contained less than 10% morphine metabolite and 88% less than 20% hydrocodone metabolite, among hydrocodone positive samples, 97% contained less than 10% hydromorphone metabolite and 95% of oxycodone positive samples contained less than 10% oxymorphone metabolite. Our analysis of opioid-positive samples may provide guidelines for interpretation of hair opioid levels typically observed in workplace testing.